Poster 213: Increased Vascularity might Peak at 3 to 6 Months Postoperatively on the Reconstructed Anterior Cruciate Ligament Assessed with Superb Microvascular Imaging (SMI). Issue 7 (30th July 2022) - Rothrauff, Benjamin; Kanto, Ryo; Byrne, Kevin; Drain, Nicholas; Fu, Freddie; Onishi, Kentaro; Takeuchi, Satoshi
Objectives: The most crucial stage of graft maturation following anterior cruciate ligament (ACL) reconstruction has been reported as the stage of revascularization. Since the strength of the reconstructed graft can be decreased during the revascularization process, graft loading during this process increases risk of graft failure. Thus, revascularization of the reconstructed graft should be monitored in order to optimize individual treatment plans and rehabilitation protocols. Contrast-enhanced magnetic resonance imaging (MRI) has been used to quantify the vascularity of the ACL in evaluating graft maturation following ACL reconstruction. Contrast enhancement in the reconstructed graft appeared at 1 month postoperatively and peaked at 4 or 6 months postoperatively. However, contrast-enhanced MRI may not be an appropriate imaging modality to evaluate postoperative revascularization at multiple timepoints due to the invasiveness of administering intravenous contrast agent coupled with its high cost and time of use. Superb Microvascular Imaging (SMI) is a novel development in ultrasound technology that allows for the detection of microvascular flow, which is difficult to detect using conventional modalities such as color and power doppler modalities. SMI allows for time- and cost-efficient assessment of the vascularity in the torn ACL, thus allowing for assessment of revascularization following ACL reconstruction. We aimed to investigate the difference in vascularity between reconstructed and intact ACLs at several postoperative timepoints following ACL reconstruction using ultrasound with SMI. Methods: A total of 30 patients (18 males; 12 females), who underwent an ACL reconstruction using quadriceps tendon autograft with patella bone block and with an intact contralateral ACL were analyzed. Patient records was retrospectively reviewed and data from SMI assessment of vascularity of the reconstructed and intact ACLs were collected. In total, 43 postoperative timepoints (1-24 months) of 30 patients were included in this study. Ultrasonographic examination was performed using a 10-3 MHz convex ultrasound transducer (Aplio i800, Canon medical systems). Patients were positioned supine with maximum knee flexion (> 90°). The ultrasound transducer was placed on the anterior aspect of the knee parallel to the longitudinal axis of the ACL, to visualize the long axis of the ACL. Following visualization of the ACL at maximal antero-posterior thickness, the vascularity of the tibial half of the ACL (within 15 mm from the tibial insertion) was assessed using SMI (Figure 1). The vascularity scale and color gain of the SMI were set to 0.8 m/s and 30-35 dB, which was chosen to minimize noise on the bony surface. A three-second video was taken and the image with the greatest vascularity signal was chosen for subsequent vascularity assessment. To quantify the amount of the vascularity signal within the region of interest (ROI), the area ratio of the vascular signal was evaluated with respect to the total area of the ROI using Image J software (vascularity ratio). The vascularity ratio was calculated by dividing the area of the vascularity signal by that of the ROI. Side-to-side difference was defined by subtracting the vascularity ratio of the intact ACL from that of the reconstructed ACL. Good to excellent intra- and inter-observer reliabilities have been confirmed for the assessment of the vascularity ratio as 0.82-0.98 (intra-class correlation coefficient). 4 Postoperative timepoints were classified into 8 sub-groups as follows: 1-2, 3-4, 5-6, 7-8, 9-10, 11-12, 12-18, and 19-24 months. Data of the vascularity ratio was compared between both ACLs and among postoperative timepoints with paired t-test and one-way ANOVA, respectively. The relationship between the vascularity of the reconstructed ACL and demographic data [age, sex, height, weight, and body mass index (BMI)] was assessed using Spearman's rank correlation coefficient or Fisher's exact test. Statistical significant was determined by p < 0.05. Results: Mean vascularity ratio of all data was significantly greater in reconstructed ACLs (0.65 ± 1.45 %) compared to intact ACLs (0.15 ± 0.51 %) (P<0.05). There was no significant correlation between the vascularity of the reconstructed ACL and demographic data. In terms of the differences among postoperative timepoints, reconstructed ACLs demonstrated significantly greater vascularity ratios at 3-4 and 5-6 months compared to other postoperative timepoints (P<0.05) (Figure 2). No significant difference was observed among any postoperative timepoints in intact ACLs (Figure 2). Significantly greater side-to-side difference of the vascularity ratio was observed at 3-4 and 5-6 months compared to other postoperative timepoints (P<0.05) (Figure 2). Conclusions: SMI was able to detect increased vascularity of reconstructed ACLs postoperatively, which was significantly greater at 3-4 and 5-6 months compared to other postoperative timepoints. Some detectable vascularity signal was observed even in the intact ACLs, which might be caused by systemic postoperative inflammatory responses or relatively increased physical activity of the uninjured knee. These results suggest that revascularization of the reconstructed graft should be evaluated based on the side-to-side difference, which may be cumbersome with contrast-enhanced MRI. Ultrasound with SMI is a non-invasive imaging modality which allows for cost- and time-efficient bilateral assessment at several postoperative timepoints and detects increased side-to-side difference of the vascularity in intact ACLs at 3-6 months postoperatively. Therefore, SMI was useful in evaluation of revascularization in the reconstructed ACL graft, which might peak at 3 to 6 months postoperatively. Figure 1. Ultrasound image with SMI showing the vascularity signals (blue area) in the reconstructed ACL. Figure 2. Vascularity ratio in reconstructed and intact ACLs as well as side-to-side difference of the vascularity ratio between both ACLs. *: Significant difference compared to the other postoperative timepoints (P<0.05)